Philosophy of Education and Sports Education Management: The Balance Between Physical Proficiency and Moral Development - Rizki, Aprilia; Ahmad, Masduki; Suryadi, Suryadi (Journal Coaching Education Sports, 2025)
This research aims to explore the balance between physical skill development and moral development in sports education through the perspective of educational philosophy. Sport education often focuses more on improving physical skills and athletic performance, so that aspects of students' moral development, such as sportsmanship, social responsibility and ethics, are often neglected. Based on a literature review and analysis of educational philosophy, especially from the thoughts of John Dewey and Aristotle, this study found that sports education based on holistic philosophical principles can serve as an effective medium for moral character building in addition to physical development. The study also explores how sport education management can design programs that are balanced between physical and moral dimensions, through the integration of moral values into the curriculum and sport practices. In addition, this study reveals the limitations of implementing this balance in many educational institutions, which often emphasize achievement over character development. The findings suggest that effective sport education not only develops physically competent students, but also ethical and socially responsible individuals. The study concludes with recommendations to strengthen the training of sport teachers and coaches in integrating moral values into physical learning.